FLIGHT LABORATORIES AND FLIGHT DATA RECORDERS (Perner's Contacts, 2011)
The aim of this paper is to familiarize the reader with the specifications of Flight Data Recorders used in aviation and used for the flight laboratory of University of Žilina, which is the part of project named:”Centre of Excellence for Air Transport” ITMS 26220120065.
Keywords: flight data recorder; aviation; flight laboratory; aircraft